2020
DOI: 10.1016/j.joca.2020.02.838
|View full text |Cite
|
Sign up to set email alerts
|

What type of exercise is most effective for people with knee osteoarthritis and co-morbid obesity?: The TARGET randomized controlled trial

Abstract: Objective: Different exercise types may yield different outcomes in osteoarthritis (OA) subgroups. The objective was to directly compare effectiveness of two exercise programs for people with medial knee OA and co-morbid obesity. Design: We performed a participant-and assessor-blinded randomized controlled trial. 128 people !50 years with medial knee OA and body mass index !30 kg/m 2 were recruited from the community. Interventions were home-based non-weight bearing (NWB) quadriceps strengthening or weight bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 47 publications
0
35
0
4
Order By: Relevance
“…Despite greater adherence to home exercise in the SMS group, we found no between-group difference in any secondary clinical outcome. Both groups either maintained or had slight diminution of the clinical improvements resulting from the preceding 12-week physiotherapist-supervised exercise phase (TARGET trial) [ 24 ]. This lack of further improvement may relate to inadequate exercise progression, including suboptimal intensities, during this unsupervised phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite greater adherence to home exercise in the SMS group, we found no between-group difference in any secondary clinical outcome. Both groups either maintained or had slight diminution of the clinical improvements resulting from the preceding 12-week physiotherapist-supervised exercise phase (TARGET trial) [ 24 ]. This lack of further improvement may relate to inadequate exercise progression, including suboptimal intensities, during this unsupervised phase.…”
Section: Discussionmentioning
confidence: 99%
“…This trial used participants completing another study, the TARGET trial [ 24 ], where participants visited a physiotherapist five times over 12 weeks for prescription of either a weight-bearing functional exercise program or a non–weight-bearing quadriceps strengthening exercise program. TARGET trial participants were recruited from the community in Melbourne, Australia, between September 2017 and May 2019 via advertisements through consumer organizations, social media, community locations, media, and our volunteer database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also some existing evidence that people with OA who are obese may experience different barriers to different types of strengthening programs. For example, our recent randomized controlled trial (RCT) found higher rates of adverse events in individuals with OA and comorbid obesity who completed a non-weight-bearing exercise program (39% of 66 participants reported an adverse event), compared to a weight-bearing functional exercise program (23% of 62 participants) (20). However, it is not clear why this is or what barriers individuals with OA who are obese face when engaging in such strengthening exercise programs.…”
Section: Introductionmentioning
confidence: 99%
“…The exercise testing plan and exercise prescription are based on findings from previous studies [39][40][41]. In detail, the neuromuscular exercises will progress in difficulty monthly, and the quadriceps exercises will progress in resistance and in the number of sets weekly from the third training, which will be determined according to a participant's pain (defined as an average pain score ≥ 4, on an 11-point numerical pain rating scale (NPRS) [42] during exercise) and perceived exertion (defined as an average exertion between 5 and 8, on an 11-point modified rating perceived exertion scale [43] during exercise).…”
Section: Exercisementioning
confidence: 99%